Do underwriters compete in IPO pricing? - LYANDRES, Evgeny (Institutional Knowledge at Singapore Management University, 2018)
We propose and implement a direct test of the hypothesis of oligopolistic competition in the U.S. underwriting market against the alternative of implicit collusion among underwriters. We construct a simple model of interaction between heterogenous underwriters and heterogenous firms and solve it under two alternative assumptions: oligopolistic competition among underwriters and implicit collusion among them. The two solutions lead to different equilibrium relations between the compensation of underwriters of different quality on one hand and the time-varying demand for public incorporation on the other hand. Our empirical results, obtained using 39 years of IPO data, are generally consistent with the implicit collusion hypothesis – banks, especially larger ones, seem to internalize the effects of their underwriting fees and IPO pricing on their rivals.